(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
In the article, studies of the kinematics and dynamics of interaction of the elements of the vibration system "slug-cut disk" are made. A mathematical model describing the trajectory of a cutting arm has been created and the technological parameters of the system at which the phenomenon of resonance occurs have been determined.